2020
DOI: 10.1097/jp9.0000000000000050
|View full text |Cite
|
Sign up to set email alerts
|

Training and learning curves in minimally invasive pancreatic surgery: from simulation to mastery

Abstract: Background: Minimally invasive pancreatic surgery (MIPS) has developed over the last 3 decades and is nowadays experiencing an increased interest from the surgical community. With increasing awareness of both the public and the surgical community on patient safety, optimization of training has gained importance. For implementation of MIPS we propose 3 training phases. The first phase focuses on developing basic skills and procedure specific skills with the help of simulation, biotissue drills, vide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 90 publications
1
23
0
Order By: Relevance
“…Most often used parameters to define learning curves were operative time (n = 51), blood loss (n = 17), and complications (n = 10). The number of procedures to surpass a first phase of learning curve was 30 for open PD, 39 for laparoscopic PD, 25 for robotic PD (P = 0.521), 16 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) for laparoscopic DP, and 15 for robotic DP (P = 0.914). In a three-phase model, intraoperative parameters improved earlier (first to second phase: operating time -15%, blood loss -29%) whereas postoperative parameters improved later (second to third phase: complications -46%, postoperative pancreatic fistula -48%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most often used parameters to define learning curves were operative time (n = 51), blood loss (n = 17), and complications (n = 10). The number of procedures to surpass a first phase of learning curve was 30 for open PD, 39 for laparoscopic PD, 25 for robotic PD (P = 0.521), 16 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) for laparoscopic DP, and 15 for robotic DP (P = 0.914). In a three-phase model, intraoperative parameters improved earlier (first to second phase: operating time -15%, blood loss -29%) whereas postoperative parameters improved later (second to third phase: complications -46%, postoperative pancreatic fistula -48%).…”
Section: Introductionmentioning
confidence: 99%
“…have been described so far. [5][6][7][8][9][10][11][12] Looking at the available surgical approaches (open, laparoscopic, and robotic), these numbers vary even further. The learning curve of a surgical procedure represents an important and underrepresented bias in clinical studies and is often neglected even in randomized controlled trials (RCT).…”
Section: Introductionmentioning
confidence: 99%
“…As RPD requires advanced surgical techniques, the optimization of training should play an important role. A recent notable review proposed a pyramid demonstrating three training phases for the implementation of minimally invasive pancreatic surgery [ 12 ]. In the first phase, the surgeon should develop basic skills and procedure-specific skills using the following tools: simulation, biotissue drills, video libraries, live case observations, and training courses.…”
Section: Resultsmentioning
confidence: 99%
“…The Miami evidence-based guidelines encourage participation in a structured training program including virtual reality simulation, biotissue training to practice dissection and anastomoses, surgical video review, and on-site proctoring [ 1 ]. Furthermore, a recent interesting review suggested the importance of the structured multimodality training system for the safe implementation of minimally invasive pancreatic surgery [ 12 ]. Therefore, a multicenter structured training system should be established for surgeons and centers to introduce RPD in Japan.…”
Section: Resultsmentioning
confidence: 99%
“…Irrespective of the technique used (stapled, hand-sewn, mixed), the creation of intestinal anastomoses is considered an advanced surgical skill [3]. This results in prolonged learning curves of minimally invasive surgical procedures involving intestinal anastomoses [4][5][6], increasing the risk for complications. Recent studies have shown increased complication rates and decreased oncological outcomes depending on the surgeon's level of technical skills [7,8].…”
mentioning
confidence: 99%